Análisis de la estructura intelectual y la evolución de la investigación en la interacción humano-computador : Un análisis bibliométrico (2019)
Bibliometrics is the application of quantitative models and methods for the understanding of research disciplines. The main concepts that are applied within the development of this type of analysis are associated to the analysis of networks and include the links, number of links and force of link within the networks of co-occurrence, co-citation, co-authorship and bibliographic links. Under these concepts and in order to visualize the evolution of human-computer interaction (HCI), a bibliometric analysis of the published literature is developed in order to know the characteristics of this body of knowledge and its development over time, understanding the evolution and trends within the research disciplines requires the combination of methods and tools that guarantee equality and replicability within these exercises. In that context, this article implements analysis is based on a systematic and exhaustive search strategy of the evolution of the HCI literature, using a combination of quantitative methods, which includes a quality analysis for the delimitation of the simple analysis of the identified publications